Implementation of the YII Framework-Based Job Training Assessment System - Andayani, Dwi; Santoso, Nuke Puji Lestari; Khoirunisa, Alfiah; Pangaribuan, Kelvin (APTISI Transactions on Management (ATM), 2021)
The current significant progress has been experienced by the publication of Information media, one of which is the scoring system. In measuring the ability of students or students in learning outcomes during the learning process assessment system is very important in an educational institution both high school and college. Universitas Raharja is one of the educational institutions that have implemented the assessment system (PEN +) online, which provides services to the lecturers of the University of Raharja in the input of the value that can be accessed anywhere and Anytime. However, nowadays for the process of the input of the value of work lecture (CTF) that has been run by students is still done manually or not computerized because lecturers still have to come to the campus to fill out a list of student value lists Submitted to the RPU. This is very inefficient, because in the assessment system PEN + lecturers have not been able to input the value of work lecture (KKP) in real time. Therefore, there is a need for development in the Coursework Assessment System (CTF) where the value of the input form is Grade. In this study there were 10 (ten) literature studies on the assessment. Thus there are 2 (two) advantages that the lecturer does not need to come to the campus to fill the form that is then handed over to the RPU and notifications for a list of values that students receive will be faster.